Quality Variation of Goji (Fruits of Lycium spp.) in China: A Comparative Morphological and Metabolomic Analysis - Yao, Ruyu; Heinrich, Michael; Zou, Yuanfeng; Reich, Eike; Zhang, Xiaolei; Chen, Yu; Weckerle, Caroline S. (Frontiers in Pharmacology, 2018)
Goji (fruits of Lycium barbarum L. and L. chinense Mill.) has been used in China as food and medicine for millennia, and globally has been consumed increasingly as a healthy food. Ningxia, with a semi-arid climate, always had the reputation of producing best goji quality (daodi area). Recently, the increasing market demand pushed the cultivation into new regions with different climates. We therefore ask: How does goji quality differ among production areas of various climatic regions? Historical records are used to trace the spread of goji production in China over time. Quality measurements of 51 samples were correlated with the four main production areas in China: monsoon (Hebei), semi-arid (Ningxia, Gansu, and Inner Mongolia), plateau (Qinghai) and arid regions (Xinjiang). We include morphological characteristics, sugar and polysaccharide content, antioxidant activity, and metabolomic profiling to compare goji among climatic regions. Goji cultivation probably began in the East (Hebei) of China around 100 CE and later shifted westwards to the semi-arid regions. Goji from monsoon, plateau and arid regions differ according to its fruit morphology, whereas semi-arid goji cannot be separated from the other regions. L. chinense fruits, which are exclusively cultivated in Hebei (monsoon), are significantly lighter, smaller and brighter in colour, while the heaviest and largest fruits (L. barbarum) stem from the plateau. The metabolomic profiling separates the two species but not the regions of cultivation. Lycium chinense and samples from the semi-arid regions have significantly (p < 0.01) lower sugar contents and L. chinense shows the highest antioxidant activity. Our results do not justify superiority of a specific production area over other areas. Instead it will be essential to distinguish goji from different regions based on the specific morphological and chemical traits with the aim to understand what its intended uses are.